ANALYZE THE STOCK PRICE OF PT. PRODIA WIDYAHUSADA TBK WAS IN THE MIDDLE OF A COVID-19 PANDEMIC OUTBREAK - Jum'an Jum'an (Cross-Border Journal of Business Management, 2021)
The purpose of this research is to analyze how the stock price conditions of PT Prodia Widyahusada TBK was in the middle of a covid-19 pandemic outbreak. The methodology used in this study uses a qualitatively descriptive method where by the methods for collecting data with the truth that have occurred or which are currently occurring without any additions to expand conclusions. So this data and information is absolutely real that comes from reliable news sources and guaranteed its validity. The results of this study showed that the share price of PT Prodia Widyahusada TBK suffered a Fluctuative . While the financial condition of the company with this Corona virus outbreak has no major effect on the company's performance because there is a health check package which society is needed.